High salt diet accelerates skin aging in wistar rats: an 8-week investigation of cell cycle inhibitors, SASP markers, and oxidative stress - Peng, Xile; Liu, Nannan; Zeng, Baihan; Bai, Yilin; Xu, Yang; Chen, Yixiao; Chen, Li; Xia, Lina (Frontiers in Bioengineering and Biotechnology, 2024)
Background Recent studies have shown that the high salt diet (HSD) is linked to increased dermal pro-inflammatory status and reduced extracellular matrix (ECM) expression in inflamed skin of mice. Decreased ECM content is a known aging phenotype of the skin, and alterations in ECM composition and organization significantly contribute to skin aging. This study aimed to determine whether a high salt diet accelerates skin aging and to identify the time point at which this effect becomes apparent. Methods Wistar rats were randomly divided into normal diet and high salt diet groups and fed continuously for 8 weeks. Skin samples were collected at weeks 7 and week 8. Skin pathological sections were evaluated and levels of cell cycle inhibitors, senescence-associated secretory phenotype (SASP), oxidative stress and vascular regulatory factors (VRFs) were examined. Correlation analyses were performed to reveal the effect of a high salt diet as an extrinsic factor on skin aging and to analyse the correlation between a high salt diet and intrinsic aging and blood flow status. Results At week 8, HSD rats exhibited thickened epidermis, thinned dermis, and atrophied hair follicles. The expression of cell cycle inhibitors and oxidative stress levels were significantly elevated in the skin of HSD rats at both week 7 and week 8. At week 7, some SASPs, including TGF-β and PAI-1, were elevated, but others (IL-1, IL-6, IL-8, NO) were not significantly changed. By week 8, inflammatory molecules (IL-1, IL-6, TGF-β), chemokines (IL-8), proteases (PAI-1), and non-protein molecules (NO) were significantly increased. Notably, despite elevated PAI-1 levels suggesting possible blood hypercoagulation, the ET-1/NO ratio was reduced in the HSD group at week 8. Conclusion The data suggest that a high salt diet causes skin aging by week 8. The effect of a high salt diet on skin aging is related to the level of oxidative stress and the expression of cell cycle inhibitors. Additionally, a potential protective mechanism may be at play, as evidenced by the reduced ET-1/NO ratio, which could help counteract the hypercoagulable state and support nutrient delivery to aging skin.